Practicality and Effectiveness of Metacognitive-Based Flipbook E-modules Assisted by GeoGebra to Improve Mathematical Conceptual Understanding of Prospective Teacher Students - Rani, Maulani Meutia; Irsal, Irni Latifa; Hidayat, Rahmat; Khairi, Annisa Ummul (Mandalika Mathematics and Educations Journal, 2025)
Starting from the low understanding of mathematical concepts of prospective teacher students in learning and the demands of the times. Prospective teachers must first understand mathematical concepts in order to easily solve more complex mathematical problems. Preliminary studies show that prospective teachers' understanding of mathematical concepts in analytical geometry is still low. Students have difficulty describing abstract geometric objects and lack access to adequate interactive learning materials, making it difficult for them to understand geometry. Teaching materials are needed in the form of metacognitive-based electronic models to improve students' understanding of mathematical concepts. This e-module supports an independent learning process that leads students to abstract mathematical problems using the help of GeoGebra. This research was conducted with the Plomp development model, to measure the level of practicality seen from the practicality questionnaire from 9 students and a lecturer teaching the Analytical Field Geometry course, and the effectiveness of the product has been seen from the small group evaluation phase. Measurement of effectiveness is measured from the average n-gain according to Meltzer to improve students' understanding of mathematical concepts. The results showed that the GeoGebra-assisted metacognitive-based electronic flipbook module to improve students' understanding of mathematical concepts was practice and effective.